Cerebrospinal fluid dynamics and intracranial pressure elevation in neurological diseases - Bothwell, Steven William (Fluids Barriers CNS, 2019)
The fine balance between the secretion, composition, volume and turnover of cerebrospinal fluid (CSF) is strictly regulated. However, during certain neurological diseases, this balance can be disrupted. A significant disruption to the normal CSF circulation can be life threatening, leading to increased intracranial pressure (ICP), and is implicated in hydrocephalus, idiopathic intracranial hypertension, brain trauma, brain tumours and stroke. Yet, the exact cellular, molecular and physiological mechanisms that contribute to altered hydrodynamic pathways in these diseases are poorly defined or hotly debated. The traditional views and concepts of CSF secretion, flow and drainage have been challenged, also due to recent findings suggesting more complex mechanisms of brain fluid dynamics than previously proposed. This review evaluates and summarises current hypotheses of CSF dynamics and presents evidence for the role of impaired CSF dynamics in elevated ICP, alongside discussion of the proteins that are potentially involved in altered CSF physiology during neurological disease. Undoubtedly CSF secretion, absorption and drainage are important aspects of brain fluid homeostasis in maintaining a stable ICP. Traditionally, pharmacological interventions or CSF drainage have been used to reduce ICP elevation due to over production of CSF. However, these drugs are used only as a temporary solution due to their undesirable side effects. Emerging evidence suggests that pharmacological targeting of aquaporins, transient receptor potential vanilloid type 4 (TRPV4), and the Na(+)–K(+)–2Cl(−) cotransporter (NKCC1) merit further investigation as potential targets in neurological diseases involving impaired brain fluid dynamics and elevated ICP.